Medical healthcare use in Parkinson's disease: survey in a cohort of ambulatory patients in Italy - Frigo Gianmario; Pacchetti Claudio; Riboldazzi Giulio; Calandrella Daniela; Michielotto Donatella; Martignoni Emilia; Cosentino Marco; Nappi Giuseppe; Lecchini Sergio (BMC, 2005)
Abstract Background Parkinson's disease (PD) is a chronic neurodegenerative disease which at present has no cure, and it usually results in severe disability. The burden of PD increases as the illness progresses, resulting in the extensive utilisation of both health and community services. Knowledge of healthcare use patterns and of their determinants may greatly contribute to improve patient care, however few studies have examined this issue in PD. The present study was devised to describe the type of and reasons for medical healthcare resource use in persons with PD attending a Centre for PD and Movement Disorders, and to examine drug prescriptions issued on such occasions. Methods The study was a retrospective, cross-sectional survey in a cohort of ambulatory patients with PD, conducted by means of standard interviews. Results In the year before the study, 92 (70.8%) of 130 patients used medical healthcare resources: 1/5 of the patients was admitted to hospital, 1/5 to emergency room, 2/5 were visited by a non-neurology specialist, and 1/4 by the GP. Reasons were: nearly 20% programmed hospital admissions and visits, and more than 25% injuries and musculo-skeletal diseases. Other conditions typically occurring in PD (e.g. dementia, diabetes and cardio- and cerebro-vascular disease) were less frequently involved. On such occasions, drugs for PD were occasionally changed, however drug prescriptions for other indications were issued to more than 66% of the patients. Conclusion Several physicians other than the neurologist may take care of PD patients on different occasions, thus emphasising the need for communication between the reference neurologist and other physicians who from time to time may visit the patient.